2015
DOI: 10.1093/jac/dkv357
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dalbavancin in the treatment of MRSA rat sternal osteomyelitis with mediastinitis

Abstract: Dalbavancin is effective in the treatment of MRSA rat sternal osteomyelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 18 publications
3
26
0
Order By: Relevance
“…Lack of source control was the primary reason for failure, as documented by persistently positive margins, wound dehiscence and persistent elevation of inflammatory markers. Dalbavancin has been shown to have high concentrations through day 14 in bone in rat studies, which is promising for clinical application [ 11 ]. Rappo et al performed a randomized clinical trial of dalbavancin in first-episode osteomyelitis treatment and found that patients treated with dalbavancin (1500 mg, 2 doses 1 week apart) had clinical cure at day 42 in 65/67 (97%) versus 7/8 (88%) in standard-of-care patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of source control was the primary reason for failure, as documented by persistently positive margins, wound dehiscence and persistent elevation of inflammatory markers. Dalbavancin has been shown to have high concentrations through day 14 in bone in rat studies, which is promising for clinical application [ 11 ]. Rappo et al performed a randomized clinical trial of dalbavancin in first-episode osteomyelitis treatment and found that patients treated with dalbavancin (1500 mg, 2 doses 1 week apart) had clinical cure at day 42 in 65/67 (97%) versus 7/8 (88%) in standard-of-care patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data on the use of dalbavancin for indications other than 1–2 doses for treatment of ABSSSI. Case reports have demonstrated success in treating more complicated infections such as MRSA pneumonia, osteomyelitis and endovascular infections [ 9 11 ]. Dalbavancin for treatment of catheter-related bloodstream infections demonstrated efficacy in a small phase 2 open-label study with overall success of 87% (95% CI 73.2–100%) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in an animal model study in which dalbavancin was compared with vancomycin for prevention of S. aureus colonization of devices, the former was more effective (Darouiche and Mansouri, 2005). Also in a recent study, dalbavancin was active in the treatment of MRSA rat sternal osteomyelitis (Barnea et al, 2016). However, in another study in which dalbavancin was tested against MRSA in a foreign-body infection model, it reduced planktonic MRSA in cage fluid at high doses, but failed to eradicate biofilms from the tissue cages (Baldoni et al, 2013).…”
mentioning
confidence: 99%
“…43 Furthermore, concerning bone drug penetration, dalbavancin effectiveness in the treatment of MRSA osteomyelitis was demonstrated in rats, showing a reduction in bone CFUs superior to placebo and similar to vancomycin. 44 No tissue accumulation after a multiple-dose regimen (1000 mg IV loading-dose on day 1 followed by 500 mg/ week for 7 weeks) was observed. 43 Dalbavancin elimination follows two routes (renal/ non-renal): after a 1000 mg single dose, in healthy volunteers, unchanged drug excretion into urine was 42% after 42 days, thus underlining the importance of non-renal elimination pathway.…”
Section: Discussionmentioning
confidence: 95%